From ultra rays to astroparticles : a historical introduction to astroparticle physics - Falkenburg, Brigitte, 1953-; Rhode, Wolfgang (Springer Science + Business Media, 2012)
In celebration of the centenary of our discovery of cosmic rays, this volume recounts the incredible story of astroparticle physics, a field full of excitement and surprise. Expert commentators from a range of disciplines explore its roots and development.